A Systematic Literature Review Based on the PRISMA Framework: The Influence of Talent Management on Employee Performance - Arie Hendra Saputro; Suwatno (Yayasan Sinergi Kawula Muda, 2026)
Talent management has emerged as a strategic approach to improving employee performance; however, previous empirical findings remain fragmented and methodologically diverse, limiting a comprehensive understanding of its overall impact. This study aims to systematically examine the relationship between talent management and employee performance while identifying dominant methodological trends in the literature. Using a systematic literature review approach, relevant articles published in reputable academic databases were analyzed based on predefined inclusion and exclusion criteria. The findings indicate that talent management consistently contributes to enhancing employee performance through improved employee engagement, competency development, organizational commitment, and retention. Nevertheless, these findings should be interpreted as indicative patterns rather than definitive causal relationships due to variations in research designs and analytical approaches across studies. In addition, the review reveals that quantitative methods dominate previous research, while integrative and longitudinal perspectives remain limited. This study contributes to clarifying the current state of evidence, identifying methodological limitations, and offering practical implications for organizations in developing more adaptive and sustainable talent management strategies, while also recommending future research using longitudinal designs, mixed-method approaches, and more rigorous analytical integration.